TINJAUAN HUKUM ISLAM DAN HUKUM POSITIF TERHADAP ABORSI BAGI WANITA KORBAN PEMERKOSAAN - Ardina; Nurinayah (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2022)
This study aims to identify and analyze legal norms, especially those related to Islamic law and positive law in Indonesia regarding abortion as a result of rape. In general, the legal status of abortion according to Islamic law is haram. Likewise, it is found in article 346 of the Criminal Code that abortion is also not permitted. However, regarding the legal status of abortion caused by rape, there are several opinions in Islamic law and positive law in Indonesia. The research in this thesis uses normative juridical research (normative legal research), namely legal research conducted by examining literature or secondary data. In accordance with the characteristics of the study, this study used the library research method (literary study). The results of the study show that the legal status of abortion as a result of rape according to Islamic law has several opinions. The Tarjih Muhammadiyah Council forbids abortion as a result of rape, the Bahtsul Masail NU and the MUI fatwa allow it. Whereas in positive law in Indonesia as contained in Law Number 36 of 2009 concerning Reproductive Health both allow abortion due to rape.